THE TIME TO IRRIGATE A BATATAL GRASS USING WATER STRESS DAILY INDEX - Turco, Jose Eduardo Pitelli [UNESP]; Furlani, Carlos Eduardo Angelini [UNESP]; Oliveira, Jean Lucas Pereira [UNESP]; Cardoso, José Ricardo Ferreira [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2022)
With this study, the objective was to study the Water Stress Daily Index (WSDI) of batatal grass to establish a value that determines the ideal time for irrigation. They were evaluated environmental weather data, water stress index plants using an infrared thermometer, and water potential in the soil. The research was conducted in the experimental area of the Department of Engineering and Mathematical Sciences FCAV/UNESP Jaboticabal Campus, in the winter period of 2019. An experiment was installed containing two treatments: T1-without irrigation, T2-irrigation performed according to the sum of the culture evaporation and irrigated when the available water capacity of the soil reached 50%, and T3-irrigation performed according to the sum of the culture evaporation keeping the soil always at field capacity. They were made 16 readings for each treatment by measuring the temperature of the vegetation cover and air temperature, held near solar noon, with the use of an infrared thermometer. The analysis was performed on the spot. According to the results, the average value of the WSDI is 8.8°C, to irrigate the T2 treatment.
MOMENTO DE IRRIGAR A GRAMA BATATAIS UTILIZANDO ÍNDICES DE ESTRESSE HÍDRICO
Keywords: grass; management of water and soil; solar radiation